The intricate dance: host autophagy and Coxiella burnetii infection - Wang, Tingting; Wang, Chao; Li, Chang; Song, Lei (Frontiers in Microbiology, 2023)
Q fever is a zoonotic disease caused by Coxiella burnetii, an obligatory intracellular bacterial pathogen. Like other intracellular pathogens, C. burnetii is able to survive and reproduce within host cells by manipulating host cellular processes. In particular, the relationship between C. burnetii infection and host autophagy, a cellular process involved in degradation and recycling, is of great interest due to its intricate nature. Studies have shown that autophagy can recognize and target intracellular pathogens such as Legionella and Salmonella for degradation, limiting their replication and promoting bacterial clearance. However, C. burnetii can actively manipulate the autophagic pathway to create an intracellular niche, known as the Coxiella-containing vacuole (CCV), where it can multiply and evade host immune responses. C. burnetii promotes the fusion of CCVs with lysosomes through mechanisms involving virulence factors such as Cig57 and CvpF. This review summarizes the latest findings on the dynamic interaction between host autophagy and C. burnetii infection, highlighting the complex strategies employed by both the bacterium and the host. A better understanding of these mechanisms could provide important insights into the development of novel therapeutic interventions and vaccine strategies against C. burnetii infections.